Podcast as a Learning Media for Tropical Nursing Vocabulary: Development and Implementation for Nursing Students - Tantry Ajeng Parnawati; Sirli Mardianna Trisinta; Swaidatul Masluhiya AF (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
English proficiency is a vital skill for nursing students to compete in the global health sector. In Indonesia, where tropical diseases remain a major health challenge with high mortality rates, nurses must master English vocabulary related to tropical nursing to better access scientific literature and international practices. Unfortunately, existing learning materials for this purpose are limited and lack contextual relevance. This study aims to develop and implement a podcast grounded in local wisdom as a medium for learning tropical nursing vocabulary among nursing students. It also examines students’ perceptions of the podcast in terms of Benefits, Content quality, Accessibility and convenience, Learning effectiveness.  The research applies the 4D development model (Define, Design, Develop, and Disseminate). The participants were 91 nursing students from Universitas Tribhuwana Tunggadewi (Malang) and Institut Kesehatan dan Bisnis (Surabaya), representing rural and urban backgrounds. Data were collected using a Likert-scale questionnaire supported by interviews.The findings indicate that the podcast can support students in enriching their tropical nursing English vocabulary. Students showed positive perceptions of the podcast, particularly regarding its benefits, content quality, and accessibility as a learning medium for tropical nursing vocabulary. Further research is expected to develop more relatable podcast episodes and to measure the effectiveness of podcasts in improving students’ English vocabulary.